Social identity on public landscapes: language mixing and cultural expressions of the graffitis in an Indonesian sport center (Conference on English Language Teaching, 2025)
This study explores the linguistic and cultural dynamics of graffiti in the public space of Gelora Satria Stadium (GOR Satria Purwokerto), Indonesia, focusing on language mixing as a means of social identity expression. Data were collected through direct onsite photographic documentation of graffiti and scribbles in the area, adhering to established linguistic landscape methodologies that prioritize authentic visual data collection. A qualitative analysis was conducted to examine textual and visual elements, categorizing instances of language use, mixing patterns, and identity indicators. Drawing on Landry and Bourhis’s (1997) theoretical framework, which differentiates the symbolic and informational functions of language in public spaces, this study interprets graffiti as a complex linguistic landscape where language choices reflect sociocultural meanings and community belonging. The findings reveal a rich interplay of local Indonesian, regional slang, and global English influences within the graffiti, demonstrating a dual identity that bridges local cultural roots and global popular culture. Notably, local affiliations are expressed through terms like “Viking Independent Crebond” and “PWG,” signaling community pride and regional belonging. Simultaneously, references to global cultural icons such as “X-Man” and “Anti-Hero” illustrate the writers’ engagement with wider cultural narratives. This blending of languages and cultural references underscores graffiti’s symbolic function as a medium for asserting both individual and collective identities in a contested public space. Ultimately, this research highlights graffiti at Gelora Satria Stadium as an active site of cultural expression and identity negotiation, emphasizing the role of linguistic landscapes in urban settings as platforms where language transcends communication to become a tool for social meaning-making and resistance.